Genetic diversity and population structure of the common bottlenose dolphin (Tursiops truncatus) in two areas of the Colombian and Panamanian Caribbean inferred from mitochondrial control region (2017)
The common bottlenose dolphin (Tursiops truncatus) is a cosmopolitan species distributed widely, so it has been reported two forms or ecotypes: the "inshore form" and the "worldwide distributed form" (WDF). Although this is one of the most studied cetaceans, several coastal populations are poorly studied. Indeed, the gap of genetic information in the Atlantic Sea is one of the main obstacle for their conservation to local level. Particularly in the Colombian Caribbean, there is not genetic studies related with bottlenose dolphins, and most studies have been focused in occurrence and habitat use. In this study, we used 18 skin samples from bottlenose dolphins obtained using a remote biopsy system (PAXARMS), and through of molecular tools we assessed the genetic diversity and population structure of two populations, one located in Bocas del Toro (BDT) (Panama, n=15) and the other one in La Guajira (Colombia, n=3). This was accomplished through amplification of a partial portion of mitochondrial Control Region (~750 pb). The haplotypes obtained were compared to previously published sequences from the Caribbean (n=43). The samples from Bocas del Toro shared the same unique "inshore" haplotype reported previously for this area, and samples from La Guajira represent three new haplotypes of the WDF, not reported before in the Caribbean. Analyses of population structure revealed two population units for the Caribbean: BDT(Panama)-Bahamas-Cuba-Mexico and Colombia-CostaRica-Honduras-PuertoRico. Our results suggest that dolphins in La Guajira are grouped only with individuals of the WDF, and not with individuals of both "inshore form" and WDF, as it has been reported previously. These findings show the importance of genetic studies in the Caribbean to assess the real conservation status of T. truncatus. Furthermore, our findings suggest that La Guajira is a transient area for bottlenose dolphins in the Caribbean. More studies are needed to confirm these hypotheses